2011
DOI: 10.1002/jbmr.345
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin is a locally acting regulator of late-osteoblast/preosteocyte differentiation and regulates mineralization through a MEPE-ASARM-dependent mechanism

Abstract: The identity of the cell type responsive to sclerostin, a negative regulator of bone mass, is unknown. Since sclerostin is expressed in vivo by mineral-embedded osteocytes, we tested the hypothesis that sclerostin would regulate the behavior of cells actively involved in mineralization in adult bone, the preosteocyte. Differentiating cultures of human primary osteoblasts exposed to recombinant human sclerostin (rhSCL) for 35 days displayed dose- and time-dependent inhibition of in vitro mineralization, with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
225
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(260 citation statements)
references
References 64 publications
(138 reference statements)
28
225
0
7
Order By: Relevance
“…It is also possible that transgenic chronic overexpression of Sost triggers a negative feedback effect, which counters the effect on osteoclast activity. This is supported by our observations in human primary osteocyte-like cells that SCL only transiently upregulated the RANKL:OPG mRNA ratio cells, and by our published observation that SCL down-regulates the expression at least one of the known receptors for SCL, LRP4 [36]. It will be of interest in future studies to examine acute versus chronic administration of sclerostin in vivo.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…It is also possible that transgenic chronic overexpression of Sost triggers a negative feedback effect, which counters the effect on osteoclast activity. This is supported by our observations in human primary osteocyte-like cells that SCL only transiently upregulated the RANKL:OPG mRNA ratio cells, and by our published observation that SCL down-regulates the expression at least one of the known receptors for SCL, LRP4 [36]. It will be of interest in future studies to examine acute versus chronic administration of sclerostin in vivo.…”
Section: Discussionsupporting
confidence: 72%
“…We previously showed that human osteocytelike cells were sensitive to the anti-anabolic effects of SCL at concentrations as low as 1 ng/ml, concentrations that are higher than but near to the levels reported in human serum of between 0.3 and 0.6 ng/ml [49,50,51]. This suggested that cells at the preosteocyte and osteocyte stages are major physiological targets for SCL [36]. In the present study, we found that SCL levels of 10 ng/ml or higher produced catabolic activity in these cells, increasing RANKL and decreasing OPG expression.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Sclerostin was also significantly decreased in the serum of HMWKO mice. Sclerostin also functions to inhibit bone formation through modulation of the Phex/Mepe ASARM pathway (38) by increasing Mepe-ASARM protein that competitively binds with Phex inhibiting activation of Dmp1 (26). Activated Dmp1 is able to nucleate hydroxyapatite crystals during the initiation of bone formation (39).…”
Section: Discussionmentioning
confidence: 99%